Chemical Composition and Biological Activities of Essential Oils from Fresh Vismia guianensis (Aubl.) Choisy and Vismia cayennensis (Jacq.) Pers. Leaves (Research, Society and Development, 2021)
The Vismia Vand. genus encompasses many species indigenous to the Amazon rain forest where they are popularly known as “Lacre” bark and leaves are widely employed by locals to treat dermatophytoses. The aim of this study was to investigate the chemical composition of essential oils (EOs) extracted from the aerial parts of the species Vismia guianensis (Aubl.) Choisy and Vismia cayennensis (Jacq.) Pers. and to assess their antimicrobial activity against the bacteria Staphylococcus aureus Rosenbach 1884 and Escherichia coli (Migula 1895) Castellani and Chalmers 1919 as well as the fungi Candida albicans (C.P. Robin) Berkhout 1923 and Candida parapsilosis (Ashford) Langeron & Talice 1932. The analysis of the chemical composition of the essential oil extracted from V. guianensis leaves (EOVg) indicated 46 components, of which three sesquiterpenes predominated, namely: (E)-caryophyllene (10.40%), α-copaene (29.45%), and (E)-nerolidol (24.06%). As to the essential oil from V. cayennensis leaves (EOVc), 61 components were identified, of which two oxygenated sesquiterpenes stood out as the main components, namely, germacrone (25.42%) and curzerene (25.29%). EOVg exhibited Minimum Inhibitory Concentration (MIC) of 1.56 µg/mL against the yeast C. parapsilosis whereas EOVc was active against the bacteria E. coli and S. aureus as well as the yeast C. parapsilosis. The results obtained in this study strongly recommend further research on the essential oils in question with a view to isolating and identifying the components responsible for their observed antimicrobial activities.